Protocol for a prospective observational study of cortical lower urinary tract control changes following intradetrusor injection of botulinum toxin-A in patients with multiple sclerosis. Issue 2 (3rd February 2017) - Elizondo, Rodolfo A; Karmonik, Christof; Boone, Timothy B; Khavari, Rose
Abstract : Introduction: Multiple sclerosis (MS) is a severe debilitating disease that affects patients' quality of life. Up to 90% of patients with MS will develop lower urinary tract dysfunction within the first 18 years of the disease. If oral pharmacotherapy with anticholinergics, behavioural modifications and pelvic floor physical therapy are unsuccessful, intradetrusor injection of botulinum toxin-A (OnaBotA; Botox Allergan, Dublin, Ireland) is a highly effective option for these patients. The local effects of OnaBotA are well understood, but not much is known of its afferent/sensory effects while treating the end organ. Our study will use functional MRI (fMRI) and task-related blood oxygen level-dependent signals to evaluate patients with MS and neurogenic detrusor overactivity (NDO) prior to, and after, intradetrusor injection of OnaBotA with simultaneous urodynamic evaluation. Urinary concentration of brain-derived neurotrophic factor and nerve growth factor will also be collected since it has been shown that patients with an overactive bladder have higher concentrations of these neuropeptides. Methods and analysis: Female patients with MS and lower urinary tract symptoms who previously have undergone urodynamic screening and are refractory to conservative and oral pharmacotherapy management for NDO and are interested in OnaBotA intradetrusor injection will be invited to participate in the study. An fMRI will be performed preintradetrusor injection and postintradetrusor injection of OnaBotA with simultaneous MRI compatible with material urodynamics. Images will be collected and analysed accordingly. Ethics and dissemination: All of the patients are properly consented before enrolling in this study that has been previously approved by the Institutional Review Board. Results of neural connectivity activation will be presented at national and international meetings and published in scholarly journals.